Depression, suicidal ideation and suicide risk in German veterinary medical students compared to the German general population. - Nadine Schunter; Heide Glaesmer; Luise Lucht; Mahtab Bahramsoltani (PLoS ONE, 2022)
Background Various studies from different countries indicated that veterinarians have a significantly increased risk of depression, suicidal ideation and of death by suicide. For German veterinarians a recent study has demonstrated a three times higher rate for depression, two times higher rate for suicidal ideation and a five times higher suicide risk compared to the German general population. For veterinary students, recent studies in the US and UK indicated higher mental distress. To date, empirical studies on depression, suicidal ideation and suicide risk among veterinary students in Germany were lacking so far. This study investigates depression, suicidal ideation and suicide risk of veterinary students in Germany. Methods 913 German veterinary students (14.3% response rate, 90.7% women, mean age 23.6 years) between 18 and 46 years were included and compared with representative German general population samples from 2007 (N = 1097, 55.4% women, mean age 33.9) and 2015 (N = 1033, 56.1% women, mean age 32.8) of the same age range using the depression module of the Patient Health Questionnaire (PHQ-9) and Suicide Behaviors questionnaire-Revised (SBQ-R). The general population samples were collected with the assistance of a demographic consulting company. Results The prevalence of depression among German veterinary students was 45.9% (compared to 3.2% in the general population), suicidal ideation was 19.9% (compared to 4.5% in the general population) and suicide risk was 24.0% (compared to 6.6% in the general population). Conclusion In this study, German veterinary students have a 22.1 times higher risk to be screened positive for depression, a 4 times higher risk for reporting current suicidal ideation and they are 4.2 times more likely to have an increased suicide risk compared with the general population in Germany of the same age range.